Diagnostic cut‐off value for Aspergillus fumigatus‐ and flavus‐specific IgG with clinical relevance in chronic pulmonary Aspergillus infection: A pilot study in Taiwan. Issue 10 (23rd August 2020) - Huang, Shiang‐Fen; Li, Shi‐Yi; Chan, Yu‐Jiun; Huang, Yu‐Chi; Yang, Ying‐Ying; Wang, Fu‐Der
Abstract: Background: The diagnostic cut‐off value for chronic pulmonary Aspergillosis (CPA) by Aspergillus fumigatus ‐specific IgG has never been evaluated In Taiwan. The cut‐off value for Aspergillus flavus ‐specific IgG has not been evaluated worldwide. Objectives: Evaluate diagnostic cut‐off value of Aspergillus IgG and its application characteristics. Patients/Methods: Blood from control groups and treatment‐naïve patients with CPA infections was collected for Aspergillus ‐specific IgG measurements. Controls were patients who had chest radiographic abnormalities and signs of respiratory tract infection, but were negative for Aspergillus and resolved without anti‐mould therapy. Confirmation and probability of CPA were defined according to radiological features and positivity for an Aspergillus or galactomannan index. Chest computer tomography patterns were recorded for the presence of aspergilloma or nodules, subacute invasive aspergillosis, chronic cavitary pulmonary aspergillosis and chronic fibrotic pulmonary aspergillosis. Results: A total of 35 cases and 50 disease controls were included. The levels of A. fumigatus ‐ and A. flavus ‐specific IgG correlated with CPA progression ( P  < .05) but not with the presence of Aspergillus species from clinical specimens ( P  > .05). The best cut‐off value for A. fumigatus IgG was 21.7 mg/L with area under curve (AUC) for receiver operating characteristic curve (ROC) 0.934 and had 85.7% sensitivity and 92.0% specificity. For A. flavus IgG, the best cut‐off value was 22.1 mgA/L and the AUC was 0.928 with 88.2% sensitivity and 94.1% specificity. Conclusion: The level of Aspergillus ‐specific IgG correlated with radiographic characteristics in patients with CPA and the best cut‐off values compared to controls were 21.7 mgA/L for A. fumigatus ‐specific IgG and 22.1 mgA/L for A. flavus ‐specific IgG.